Pengaruh Rasio Keuangan Terhadap Return on Asset dengan Capital Adequacy Ratio sebagai Variabel Moderating pada Bank Perkreditan Rakyat di Kepulauan Riau - Harifda; Satriawan, Bambang; Puspita Dewi, Nolla (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Technological developments, especially with the emergence of the internet and digital devices, have brought major changes to the world of banking. People's Credit Banks (BPR) have an important role in supporting community businesses, especially at the local or regional level. The following are some of the main roles played by BPR Banks in supporting community businesses. Research carried out at people's credit banks (BPR) in the Riau Islands registered with the OJK throughout 2019-2023. In this research, the author used the purposive method technique, which is a technique chosen by the researcher to achieve the researcher's objectives with the criteria that have been set so that there are 17 companies that meet the criteria. Based on the processed data obtained in the field, the final research results were found to be non- Performing Loans (NPL) have a direct significant effect on Return on Assets (ROA), Loan To Deposit Ratio (LDR) do not have a direct significant effect on Return on Assets (ROA) at Rural Banks (BPR) Batam City, Operational Costs Operational Income (BOPO) has a direct significant effect on Return On Assets (ROA) at Rural Banks (BPR) in Batam City, Capital Adequacy Ratio (CAR) does not significantly moderate between Net Performing Loans (NPL) and Loan To Deposit Ratio (LDR) on Return on Assets (ROA) at Rural Banks (BPR) in Batam City and the Capital Adequacy Ratio (CAR) significantly moderate the relationship between Operational Costs and Operating Income (BOPO) against Return On Assets (ROA) at Rural Credit Banks (BPR).